Własne doświadczenia w leczeniu chorych ze złamaniem rozprężającym oczodołu - Wyszyńska-Pawelec, Grażyna; Zapała, Jan; Kubatko-Zielińska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2005)
The aim of the paper is to present long-term experience in multidisciplinary treatment of patients with orbital blowout fracture (OBF). Material and methods: from 1971 to 2003, 344 patients, including 148 children, with OBF were treated. Diagnostics comprised of ophthalmologic examination, including instrumental methods and radiology. Treatment comprised of primary reconstruction of the orbit, orthoptic rehabilitation and in cases of failure eye muscle surgery or prismatic correction. The aim of primary reconstruction of the orbit was to restore full passive motility of the eyeball and reconstruction of orbital bones. Results: recovery was obtained in 40.1% of patients, marked improvement in 29.4% and improvement in 27.3% of patients. Conclusions: Surgical treatment of patients with OBF is indicated in patients with persistent diplopia concomitant with restricted passive eyeball motility.